The Effect of Moisture and Fine Grain Content on the Resilient Modulus of Sandy Clay Embankment Roadbed - Tuan, N. A.; Chieu, P. Q. (Engineering, Technology & Applied Science Research, 2021)
This paper studies the effect of moisture and fine grain content on the resilient modulus of sandy clay embankment roadbed in the Mekong Delta, Vietnam. The study analyzed the grain content of 30 soil samples on the annually flooded routes of the Mekong Delta according to the AASHTO T88-97 standard. The triaxial compression test at room temperature was used to estimate the resilient modulus of the samples belonging to 6 moisture levels. The experiments were conducted using 3 levels of lateral pressure, 0, 21, and 41kPa. Five deflection stress tests of 14, 28, 41, 55, and 69kPa, were conducted for each lateral pressure. The results showed that as the percentage of grains finer than 0.075mm increased, the variation ratio of the resilient modulus also increased. The content of grains finer than 0.075mm was between 54.1%-93%, while the variation ratio of the resilient modulus ranged between 53.7% and 89.1%. Moreover, as the percentage of grains finer than 0.075mm increased, water absorption capacity increased and resilient modulus decreased. As moisture and fine grain content influence the resilient modulus of the roadbed, this study’s results will help to limit and prevent the erosion of sandy clay embanked roadbeds, especially on frequently flooded areas such as the Mekong Delta.